Preliminary Survey of Lizards of Pantai Melawi, Bachok, Kelantan, Malaysia - Diah, S.Z.M.; Hashim, Rosli; Yong, Hoi Sen; Belabut, D.; Dzarawi, N.S. (Faculty of Science, University of Malaya, 2010)
A survey of lizards was conducted of Pantai Melawi, Bachok on 12-14 April and 11-13 May 2009. Nine species of lizards were recorded in this preliminary survey. They were from the family Agamidae (Calotes versicolor, Leiolepis belliana), family Gekkonidae (Cosymbotus platyurus, Gehyra mutilata, Gekko monarchus, Gekko gecko and Hemidactylus frenatus), family Scincidae (Eutropis multifasciata) and family Varanidae (Varanus salvator). The common species in this area were Leiolepis belliana and Hemidactylus frenatus. Pemerhatian cicak dijalankan di Pantai Melawi, Bachok pada 12-14 April dan 11-13 Mei 2009. Sembilan spesies cicak telah direkodkan dalam bancian awal ini. Cicak yang dikenalpasti adalah dari famili Agamidae (Calotes versicolor, Leiolepis belliana), famili Gekkonidae Cosymbotus platyurus, Gehyra mutilata, Gekko monarchus, Gekko gecko dan Hemidactylus frenatus), famili Scincidae (Eutropis multifasciata) dan famili Varanidae (Varanus salvator). Spesies yang umum di kawasan ini ialah Leiolepis belliana dan Hemidactylus frenatus.